Regional Disparities in the Incidence of Taxation in Uganda - Elkan, Walter (Review of Economic Studies, 1959)
Journal Article Regional Disparities in the Incidence of Taxation in Uganda Get access Walter Elkan Walter Elkan Makerere College Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 26, Issue 2, February 1959, Pages 135–147, https://doi.org/10.2307/2296171 Published: 01 February 1959